Table of Content - - (Journal of engineering sciences and information technology, 2023)
Table of Content:1. Evaluating the policy of removal and resettlement for residents of unsafe slums in greater Cairo according to the principles of sustainable development. Case study of Asmarat neighborhood.Eng. Mohamed Sobhi Abdel Ghani Hassan, Prof. Mohamed Abdel-Baqy Ibrahim , Prof. Ghada Farouk Hassan , Prof. Marwa Aboul Fotouh Khalifa2. Railways Projects Appraisal Using Reference Class Forecasting and Fuzzy Sets TheoryEng. Dana Marwan Al Sheikh, Dr. Jamal Yunus Omran , Dr. Mudar Ali Alaaraj3. Measure Effectiveness of SMS Spam Detection Model Based on Machine Learning TechniquesEng. Ahmed Hamed Osman, Dr. Muhammad Badawi Al-Khalifa4. Study the Effect of Electromagnetic Radiation towards Sustainable Healthy BuildingsLecturer \ Sara N. Elkabany5. Energy efficiency of conventional air conditioning systems in light of climate changeEng. Fawaz Khaled Ghaith
Keywords: Journal of Engineering Sciences and Information Technology